2014
DOI: 10.1007/s40142-014-0047-5
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Genetic Discovery and Implications for Counseling of Patients and Families with Autism Spectrum Disorders

Abstract: The prevalence of autism spectrum disorders (ASD) continues to increase. Genetic factors play an important role in the etiology of ASD, although specific genetic causes are identified in only a minority of cases. Recent advances have accelerated the discovery of genes implicated in ASD through convergent genomic analysis of genome-wide association studies, chromosomal microarray, exome sequencing, genome sequencing, and gene networks. Hundreds of candidate genes for ASD have been reported, yet only a handful h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 105 publications
(93 reference statements)
0
8
0
Order By: Relevance
“…Previous research found that parents expressed interest in using genetic testing to assess the risk of ASD in younger siblings of affected children (Chen et al 2013; Narcisa et al 2012), and this is frequently reported as a major potential value of genomic testing for ASD (Schaefer and Mendelsohn 2013; Shen et al 2010, 2014). Parents in our study did not report using results for this purpose, explaining that younger siblings were either already diagnosed with ASD or were not displaying potential symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research found that parents expressed interest in using genetic testing to assess the risk of ASD in younger siblings of affected children (Chen et al 2013; Narcisa et al 2012), and this is frequently reported as a major potential value of genomic testing for ASD (Schaefer and Mendelsohn 2013; Shen et al 2010, 2014). Parents in our study did not report using results for this purpose, explaining that younger siblings were either already diagnosed with ASD or were not displaying potential symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic testing is not considered a diagnostic test for ASD, however, several studies have demonstrated the clinical utility of CMA in terms of changes in clinical management and medical care (Agency for Healthcare Research and Quality (AHRQ) 2014; Beaudet 2013; Coulter et al 2011; Ellison et al 2012; Hayeems et al 2014; Henderson et al 2014; Mefford et al 2012; Riggs et al 2014; Shen et al 2010). The identification of underlying genetic etiology can be used to guide counseling about recurrence risk in the family, aid in establishing prognosis, tailor the care of affected individuals, shorten the ‘diagnostic odyssey,’ and facilitate access to appropriate early interventions (Dawson et al 2010; Eriksson et al 2013; Hayward et al 2009; Heil and Schaaf 2013; Lintas and Persico 2009; Narcisa et al 2012; Reiff and Mulchandani 2015; Shen et al 2010, 2014; Warren et al 2011). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the cause, associated medical risks may be identified and guide screening or medical interventions to prevent comorbid conditions (Schaefer & Mendelsohn, 2013). Genetic information can inform recurrence risk counseling for parents who may be considering having another child (Shen, Lincoln, & Miller, 2014), and may also help to identify younger siblings at risk of ASD, and to initiate early interventions (Miller et al, 2010;Shen, 2010;Shen et al, 2014). A causal genetic explanation can be helpful for some parents in alleviating self-blame and feeling empowered to obtain support, whereas others may feel burdened by this knowledge or have difficulty understanding the information (Reiff et al, 2012).…”
Section: Purpose Of Genetic Testing In Individuals With Asdmentioning
confidence: 99%
“…The prevalence of genetic diagnoses among child psychiatry patients is best studied for autism, where 10–20 % of cases have a diagnosable genetic cause [e.g. Fragile X (FXS)] [ 1 6 ]. There is little information about the prevalence of genetic conditions in child psychiatry patients more generally.…”
Section: Introductionmentioning
confidence: 99%